The Role of Pharmacogenetic-Based Pharmacokinetic Analysis in Precise Breast Cancer Treatment - Xinyu Wu; Huihua Xiong (MDPI AG, 2024)
Given the high prevalence of breast cancer and the diverse genetic backgrounds of patients, a growing body of research emphasizes the importance of pharmacogenetic-based pharmacokinetic analysis in optimizing treatment outcomes. The treatment of breast cancer involves multiple drugs whose metabolism and efficacy are influenced by individual genetic variations. Genetic polymorphisms in drug-metabolizing enzymes and transport proteins are crucial in the regulation of pharmacokinetics. Our review aims to investigate the opportunities and challenges of pharmacogenomic-based pharmacokinetic analysis as a precision medicine tool in breast cancer management.